The Impact of Accounting Automation on the Role of Human Accountants in Multinational Companies - Sudaryat; Anisa Putri; Ana Rusmardiana (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores the impact of accounting automation on the role of human accountants in multinational companies, focusing on the transformative effects of technologies such as Robotic Process Automation (RPA), Artificial Intelligence (AI), and Machine Learning (ML). Using a qualitative approach, specifically a systematic literature review (SLR) and library research, the study examines existing academic articles, industry reports, and case studies to assess how automation has reshaped accounting practices in multinational corporations. The findings reveal that automation has significantly enhanced operational efficiency, reduced human error, and streamlined accounting processes, leading to cost savings and more accurate financial reporting. Additionally, the role of accountants has shifted from performing routine, operational tasks to more strategic and advisory functions, contributing to business decision-making and financial strategy. However, the study also highlights concerns regarding job displacement, particularly for lower-level accounting roles, and emphasizes the need for continuous professional development and skill acquisition in areas such as AI and data analytics. The study concludes that while automation offers substantial opportunities for accountants to grow in strategic roles, it also requires significant adaptation in terms of skills and responsibilities. Future research is recommended to explore the long-term effects of automation on the accounting profession, its ethical implications, and the effectiveness of training programs aimed at equipping accountants with the necessary technological skills.